Successful Same-Cycle Blastocyst Transfer following Laparoscopic Ovarian Detorsion: A Report of Two Cases and Literature Review - Mohamad Irani; Reshef Tal; David B. Seifer; Richard V. Grazi (Hindawi Limited, 2014)
Ovarian stimulation increases the risk of ovarian torsion. During an in vitro fertilization (IVF) cycle, the effects of ovarian torsion on retrieved oocytes and subsequent pregnancy chances are not clear. Moreover, no cases of ovarian torsion occurring following oocyte retrieval but prior to same-cycle embryo transfer have been reported. Such cases present a clinical dilemma with respect to optimal timing of embryo transfer. We report two cases of a 41-year-old and a 32-year-old infertility patients undergoing IVF who were diagnosed with ovarian torsion within several days following oocyte retrieval. Both patients were treated by early laparoscopic evaluation and detorsion followed by day five embryo transfer, resulting in successful pregnancies. Therefore, after prompt laparoscopic ovarian untwisting of a torsed ovary following egg retrieval, embryo transfer may be performed as originally scheduled during the concurrent cycle leading to favorable pregnancy outcomes.